Performance and outcomes of noninvasive prenatal testing for twin pregnancies in Japan. Issue 10 (17th July 2018) - Takeda, Eri; Suzumori, Nobuhiro; Kumagai, Kyoko; Inuzuka, Saki; Oseto, Kumiko; Ohigashi, Yuka; Yotsumoto, Junko; Miyake, Hidehiko; Sugiura‐Ogasawara, Mayumi
Abstract: Aim: The purpose of this study was to describe the characteristics of women with twin pregnancies who undergo noninvasive prenatal testing (NIPT) as well as the post‐partum and neonatal outcomes of such cases in Japan. Methods: The study population consisted of women who were pregnant with twins and who underwent NIPT using massively parallel sequencing (MPS) at Nagoya City University Hospital between April 2013 and June 2016. Questionnaires were completed pre‐NIPT and post‐partum. Results: Among 4009 women who underwent NIPT during the study period, 75 women (1.9%) were pregnant with twins. Fifteen women (20%) experienced vanishing twin/intrauterine fetal deaths at <22 weeks, and 60 women (80%) had normal twin pregnancies at the time of genetic counseling for NIPT. The use of NIPT was correlated with increased proportions of women using assisted reproductive technology (ART). The test had a high performance, with a false‐positive rate of 1.7% and no false negatives. Conclusion: In this study, NIPT had a high performance, with a false positive rate of 1.7% and no false negatives. When treating women with twin pregnancies, the efficacy of NIPT should be explained during genetic counseling. Further larger studies are required to assess the reliability and validity of NIPT in twin pregnancies.